PENGARUH KONSENTRASI GULA DAN LAMA FERMENTASI TERHADAP KARAKTERISTIK SARI KACANG HIJAU (Phaseolus radiatus L.) PROBIOTIK DENGAN PENAMBAHAN Lactobacillus rhamnosus SKG 34 - Sembiring, Yemima Dwi Gita; Nocianitri, Komang Ayu; Duniaji, Agus Selamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 3 (2018): Jurnal ITEPADO - 10.24843/itepa.2018.v07.i03.p03, 2018)
This research was conducted to determine the effect of sugar contentration and fermentation time to the charateristics of mung bean probiotic drink with the addition of Lactobacillus rhamnosus SKG 34. The Randomized Complete Block Design (RCBD) with two factors was used in this research. First factor was the sugar concentration which consists of three levels 2.5%, 5%, 7.5%. Second factor was the fermentation time which consists of five levels 8 hours, 10 hours, 12 hours, 14 hours and 16 hours. The parameters observed in this research were sugar level, total lactic acid, pH, total lactic acid bacteria (LAB), and sensory acceptances such as colour, flavor, taste and overall acceptance. The result of this research showed that the sugar concentration had significant effect to the total sugar but had no significant effect to the total lactic acid and pH. The fermentation time had significant effect to the pH, total lactic acid and total sugar. The interaction of sugar concentration and fermentation time had no significant effect to the characteristic of pH, total lactic acid, total sugar, color, flavor, taste and overall acceptance. Mung bean probiotic drink with the best characteristic was obtained at 5% of sugar concentration and 8 hours fermentation time with criteria sugar concentration levels at 8.06 %, total lactic acid 0.27 %, pH at 5.29, and 1.6 x 10 8 CFU/ml total LAB with sensory results state that the colour was slightly liked, the flavor was slightly liked, the taste was preferred and slightly sweet, and overall acceptance was preferred.